PELAKSANAAN SISTEM PERADILAN PIDANA ANAK DI INDONESIA PERSPEKTIF NILAI KEADILAN - Simatupang, Rajarif Syah Akbar (Jurnal Yuridis, 2024)
One of the elements that must exist in a legal and democratic state is the protection of human rights, including child protection, which will determine the future of the Indonesian state and ensure that future generations have clear regulations. This research is normative legal research, namely legal research that places law as a building block of norms. The juvenile criminal justice system is used by law enforcement to decide criminal sanctions against children who commit criminal acts or children who are in conflict with the law. The best interests of the child must be the main priority in child punishment. However, according to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Juvenile criminal justice falls under the scope of the General Court. In completing diversion and restorative justice procedures in accordance with statutory provisions for children in conflict with the law, Settlement efforts use mediation, conciliation, and restitution methods simultaneously to unite the parties in a settlement. Therefore, it is mandatory to ensure that cases of children in conflict with the law do not involve the judicial process. Instead, the case was transferred outside the judicial process (non-litigation).